Targeting senescent cells alleviates obesity‐induced metabolic dysfunction. Issue 3 (25th March 2019) - Palmer, Allyson K.; Xu, Ming; Zhu, Yi; Pirtskhalava, Tamar; Weivoda, Megan M.; Hachfeld, Christine M.; Prata, Larissa G.; van Dijk, Theo H.; Verkade, Esther; Casaclang‐Verzosa, Grace; Johnson, Kurt O.; Cubro, Hajrunisa; et al.
Abstract: Adipose tissue inflammation and dysfunction are associated with obesity‐related insulin resistance and diabetes, but mechanisms underlying this relationship are unclear. Although senescent cells accumulate in adipose tissue of obese humans and rodents, a direct pathogenic role for these cells in the development of diabetes remains to be demonstrated. Here, we show that reducing senescent cell burden in obese mice, either by activating drug‐inducible "suicide" genes driven by the p16 Ink4a promoter or by treatment with senolytic agents, alleviates metabolic and adipose tissue dysfunction. These senolytic interventions improved glucose tolerance, enhanced insulin sensitivity, lowered circulating inflammatory mediators, and promoted adipogenesis in obese mice. Elimination of senescent cells also prevented the migration of transplanted monocytes into intra‐abdominal adipose tissue and reduced the number of macrophages in this tissue. In addition, microalbuminuria, renal podocyte function, and cardiac diastolic function improved with senolytic therapy. Our results implicate cellular senescence as a causal factor in obesity‐related inflammation and metabolic derangements and show that emerging senolytic agents hold promise for treating obesity‐related metabolic dysfunction and its complications. Abstract : Obesity induces the formation of senescent cells, which contribute to inflammation, insulin resistance, and organ dysfunction. Senescent cell clearance may be an effective strategy for alleviating important elements of obesity‐related metabolic dysfunction.